2018
DOI: 10.1371/journal.pbio.3000028
|View full text |Cite
|
Sign up to set email alerts
|

The placenta goes viral: Retroviruses control gene expression in pregnancy

Abstract: The co-option of endogenous retroviruses (ERVs) is increasingly recognized as a recurrent theme in placental biology, which has far-reaching implications for our understanding of mammalian evolution and reproductive health. Most research in this area has focused on ERV-derived proteins, which have been repeatedly co-opted to promote cell–cell fusion and immune modulation in the placenta. ERVs also harbor regulatory sequences that can potentially control placental gene expression, but there has been limited evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 37 publications
0
32
0
2
Order By: Relevance
“…However, there are also numerous examples of TE sequences being co-opted for use by the host. In mammals, syncytin genes are ERV-derived envelope protein genes which are expressed by cells of the placenta during embryonic development and are involved in placental cell-cell fusion to form the characteristic placental structure (Chuong, 2018). Other placental genes such as corticotropinreleasing hormone have been shown to be regulated by ERV sequence enhancers, showing that ERV sequences are important for placental development and mammalian evolution (Chuong, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are also numerous examples of TE sequences being co-opted for use by the host. In mammals, syncytin genes are ERV-derived envelope protein genes which are expressed by cells of the placenta during embryonic development and are involved in placental cell-cell fusion to form the characteristic placental structure (Chuong, 2018). Other placental genes such as corticotropinreleasing hormone have been shown to be regulated by ERV sequence enhancers, showing that ERV sequences are important for placental development and mammalian evolution (Chuong, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, syncytin genes are ERV-derived envelope protein genes which are expressed by cells of the placenta during embryonic development and are involved in placental cell-cell fusion to form the characteristic placental structure (Chuong, 2018). Other placental genes such as corticotropinreleasing hormone have been shown to be regulated by ERV sequence enhancers, showing that ERV sequences are important for placental development and mammalian evolution (Chuong, 2018). Another recent study showed that subsets of ERV and LINE DNA sequences participate in a gene regulatory network that controls innate immune response genes downstream of interferon γ signaling (Chuong et al, 2016), suggesting important roles in host innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that, in trophoblast stem cells, RlllLTR13D5s, which comprise a mouse-specific ERVK family, have enhancer functions to establish a trophoblast stem cell-specific regulatory network, and the same study predicted the existence of enhancer-like ERVs in testes and embryonic stem cells 35 . Curiously, placenta is known to be a fast-evolving organ in which many ERVs have been co-opted 54,55 . Thus, it is intriguing to speculate that ERVs are drivers of species-specific transcriptomes in rapidly evolving organs such as the testis and placenta, although mechanisms underlying intrinsic ERV activity in testes and placenta remain undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…One important finding was the identification of Syncytin and L1-retrotransposons genes in the venom gland of B. jararaca. Syncytin genes are associated with placental evolution in mammals and viviparous anim als [ 73 ]. Up to now, these coding sequences were never described in transcriptomes of viviparous snakes, mainly B. jararaca .…”
Section: Discussionmentioning
confidence: 99%